Evaluasi karakteristik gula kelapa cair dengan variasi penggunaan laru dan penambahan ekstrak rosela - Ike Sitoresmi Mulyo Purbowati; Gunawan Wijonarko; Ali Maksum (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Coconut sugar is a food ingredient made from coconut juice. Nira is easily damaged due to microbial contamination. The destruction of sap can be prevented by the use of laru and variations of rosella constituencies. This study aims to examine the effect of the use of laru on the quality of sap and liquid coconut sugar, the effect of variations in the addition of rosella extract on the quality of liquid coconut sugar, and the influence of the combination of variations in the use of laru and the addition of rosella extract on the quality of liquid coconut sugar. This study used experimental methods with a Complete Randomized Design (RAL). The factor studied was the use of nira preservatives: Non Laru and Laru. The second factor is the variation in the concentration of added rosella extract which is 0; 5; 10; 15 %. The variables observed were pH, Brix, reduction sugar, moisture content, viscosity, colour, aroma, taste, preferences, texture and flavour. The use of laru affects the pH, reduction of sugar, colour, aroma, taste, preferences, texture and flavour of liquid coconut sugar. The higher the concentration of rosella extract administered will lead to a decrease in pH, ̊Brix, viscosity and an increase in moisture content. The higher the concentration of rosella added to liquid coconut sugar, the browner the colour of liquid coconut sugar will be, the distinctive aroma will be mushier, the sweetness is slightly reduced, the level of liking decreases, and the texture is as good as diluted and the flavour of liquid coconut sugar also decreases.